The Penggunaan Bungkil Inti Sawit dan Bungkil Kedelai Sebagai Sumber Protein dalam Pakan Konsentrat Kubus pada Kambing Kacang: Use of Palm Kernel Cake and Soybean Meal as Source of Feed Protein on Cubed Concentrate Feed - Hidayat, Hidayat; Akbarillah, Tris; Badarina, Irma (BPFP Universitas Bengkulu, 2025)
This experiment aimed to compare palm kernel meal and soybean meal as sources of rumen undegradable protein for kacang goats. Sixteen 10-month-old doeling weighing between 13-14 kg were used as experimental animals. A completely randomized design was applied to test four types of feed treatments, namely setaria grass-based feed and different cube-shaped concentrate feed (CCF), with four replications for each treatment. The four types of treatments were: P1. CCF without soybean meal, P2. CCF with soybean meal without heating, P3. CFF with soybean meal heated at 165oC for 75 minutes, and P4. CCF with soybean meal heated at 165 oC for 150 minutes. Each treatment was given a ration consisting of 50% Setaria grass as a basal feed and 50% CCF according to the treatment (on a dry matter basis). The variables observed were dry matter and nutrient intake, dry matter and nutrient digestibility, and average daily weight gain for 12 weeks. The data obtained were analyzed using analysis of variance (ANOVA) using the Systat for Windows statistical software package, if there were differences, further testing was carried out using the least significant difference (LSD) test. The results showed that nutrient intake was not significantly different (P>0.05), but the lowest digestibility value (P<0.05) was in treatment 4, CCF which used soybean meal with longer heating. The highest daily weight gain (P<0.05) was achieved by goats that received PKK palm kernel meal. It was concluded that the use of palm kernel cake in CCF gave good results, as indicated by the highest average daily gain of goat